Prepubertal unilateral gynecomastia in the absence of endocrine abnormalities - Min Kang; Chan Jae Lee; Il Tae Hwang; Kwanseop Lee; Min Jae Kang (Korean Society of Pediatric Endocrinology, 2014)
Gynecomastia is defined as the excessive development of breast tissue in males, which can occur as unilateral or bilateral. Although the overall prevalence of gynecomastia is 40%-65%, the prepubertal unilateral gynecomastia in the absence of endocrine abnormalities is unusual, with only a few case reports in literature. Idiopathic gynecomastia in prepuberty is benign but a diagnosis of exclusion. We here report two cases of healthy prepubertal boys aged 8.8 and 9.6 years old, respectively, presented with painful palpable mass in their unilateral breast. Breast tissue with glandular proliferation was confirmed on ultrasonography. Serum levels of estradiol, testosterone, and other laboratory findings were within normal range. They seem to have the prepubertal idiopathic gynecomastia but further follow-up to see their progression is needed.